Increased MET Gene Copy Number but Not mRNA Level Predicts Postoperative Recurrence in Patients with Non–Small Cell Lung Cancer() - Kowalczuk, Oksana (Transl Oncol, 2014)
The aim of the present study was to investigate the relationship of MET copy number (CN) and MET mRNA expression to other molecular alterations, clinicopathologic characteristics, and survival of patients with resected non–small cell lung cancer. One hundred fifty-one paired surgical samples of tumor and tumor-distant normal lung tissues were analyzed by comparative quantitative polymerase chain reaction (PCR) methods with commercially available assays and the CopyCaller software v. 1.0 for post-PCR data processing (downloadable from www.appliedbiosystems.com). MET copy gain (set as more than 3.0 copies per cell) was found in 18.5% of the samples and occurred more frequently in the adenocarcinomas (ADCs) with an increased epidermal growth factor receptor (EGFR) or human epidermal growth factor receptor 2 (HER2) CN (P = .001 and .030 for EGFR and HER2, respectively) and in the ADCs with EGFR activating mutations (P = .051) but did not correlate with KRAS dosage or mutational status. MET mRNA level was 1.76-fold higher [95% confidence interval (CI), 1.29-2.40] in the tumor compared to unaffected lung tissue and associated significantly with MET CN (beta coefficient, 1.51; 95% CI, 1.22-1.87; P < .001). In the multivariable analysis, patients diagnosed with ADC with increased MET CN had a significantly higher risk of disease recurrence (hazard ratio, 1.76; 95% CI, 1.20-2.57; P = .004). An increased MET CN in combination with histologic type appears to be a prognostic factor in patients with ADC after a curative surgery.